Pharmacovigilance study on the increased use of antibiotics in pediatric treatment: Pharmacovigilance of antibiotic usage - Sakhare, Ghansham R; Yelwande, Purva; Suryawanshi, Sandhya; Ambhore, Kiran; Pawar, Rutuja; Jain, Kishor (Indian Journal of Pharmacy & Drug Studies, 2023)
Objective: To conduct the pharmacovigilance study on the increased use of antibiotics in pediatric treatment. Materials and Methods: A suitable, simple questionnaire associated with the study of pharmacovigilance assessment, for mainly the adverse drug reactions associated with the increased antibiotic use in pediatric treatment was designed and distributed among 200 families having children in the age groups of